2016
DOI: 10.1016/j.atherosclerosis.2016.07.921
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is independently associated with greater prevalence of erectile dysfunction: The National Health and Nutrition Examination Survey (NHANES) 2001–2004

Abstract: Background and Aims Erectile dysfunction (ED) and atherosclerotic cardiovascular disease (ASCVD) share many common risk factors, and vascular ED is a marker for increased ASCVD risk. Low 25-hydroxyvitamin D [25(OH)D] concentrations have been associated with increased ASCVD risk, but less is known regarding the relationship of low 25(OH)D with ED. We determined whether 25(OH)D deficiency is associated with ED independent of ASCVD risk factors. Methods We performed cross-sectional analyses of 3,390 men aged ≥2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 47 publications
3
66
1
1
Order By: Relevance
“…[31] An increased risk for prevalent ED was seen for deficient levels of 25(OH)D below 20 ng/mL, while prevalence of ED decreases when VD levels are over 35 ng/mL. [9] The researchers of the latter study restricted their analysis to the 562 men (among 3,390 men) and found even stronger association between VD status and ED. [9] Unfortunately, the available literature evaluating VD supplementation and its relationship to cardiovascular health are limited in number.…”
Section: Effect Of Low Vitamin D Level On Different Body System and Fmentioning
confidence: 99%
See 4 more Smart Citations
“…[31] An increased risk for prevalent ED was seen for deficient levels of 25(OH)D below 20 ng/mL, while prevalence of ED decreases when VD levels are over 35 ng/mL. [9] The researchers of the latter study restricted their analysis to the 562 men (among 3,390 men) and found even stronger association between VD status and ED. [9] Unfortunately, the available literature evaluating VD supplementation and its relationship to cardiovascular health are limited in number.…”
Section: Effect Of Low Vitamin D Level On Different Body System and Fmentioning
confidence: 99%
“…[13] Vitamin D deficiency is one of several conditions that is associated with increased CV disease. [9,14] Research in The United States has shown that low serum VD levels are associated with a higher prevalence of peripheral arterial disease in the general population. [30] Database information of more than 7,000 VD deficient patients showed an association between VDD, many CV disease states, including hypertension, coronary artery disease, and ASCV risk factors, such as hypertension, diabetes mellitus (DM), and hyperlipidemia.…”
Section: Effect Of Low Vitamin D Level On Different Body System and Fmentioning
confidence: 99%
See 3 more Smart Citations